Study of suspension grafting process of polypropylene - Fengchun Liang; Hao Yuan; Qing Shao; Wenbo Song (Designed Monomers and Polymers, 2018)
Grafting efficiency is an important indicator of polypropylene grafting reaction. A series of studies have been accomplished, including the conditions of free radical presence on PP backbone during peroxide initiation, the effect of preheat treatment and reaction time on PP suspension grafting results, and the effect of peroxide residue on properties of modified PP. An optimized grafting process was proposed by mixing and preheating polypropylene (PP) and the initiator benzoyl peroxide (BPO) before adding the grafting monomer glycidyl methacrylate (GMA),resulting in an increase in grafting efficiency from 50.0% to 78.2%. With initiator residue removed by alternating temperature treatment, the suspension grafting reaction time could be substantially reduced.